Comparison of progress monitoring data from general outcome measures and specific subskill mastery measures for reading. (April 2018) - Van Norman, Ethan R.; Maki, Kathrin E.; Burns, Matthew K.; McComas, Jennifer J.; Helman, Lori
Abstract: Interventionists often monitor the progress of students receiving supplemental interventions with general outcome measures (GOMs) such as curriculum-based measurement of reading (CBM-R). However, some researchers have suggested that interventionists should collect data more closely related to instructional targets, specific subskill mastery measures (SSMMs) because outcomes from GOMs such as CBM-R may not be sufficiently sensitive to gauge intervention effects. In turn, interventionists may prematurely terminate an effective intervention or continue to deliver an ineffective intervention if they do not monitor student progress with the appropriate measure. However, such recommendations are based upon expert opinion or studies with serious methodological shortcomings. We used multi-variate multilevel modeling to compare pre-intervention intercepts and intervention slopes between GOM and SSMM data collected concurrently in a sample of 96 first, 44 second, and 53 third grade students receiving tier 2 phonics interventions. Statistically significant differences were observed between slopes from SSMM consonant-vowel-consonant words and CBM-R data. Statistically significant differences in slopes were not observed for consonant blend, digraph or consonant-vowel-consonant-silent e (CVCe) SSMMs. Results suggest that using word lists to monitor student response to instruction for early struggling readers is beneficial but as students are exposed to more complex phonetic patterns, the distinction between SSMMs and CBM-R become less meaningful.